Effects of Antidepressive Medication on Lung Forced Expiratory Flow Rate in Patients with Major Depressive Disorder - Afreen, Khandaker Nadia; Imtiaz, Masud; Rouf, Mahadi Abdur; Juaira, Tasneema; Akhter, Tahmina; Akhter, Marufa (KYAMC Journal, 2017)
Background: Major Depressive Disorder (MDD) is associated with depressed lung function. Objectives: To observe FEF25%-75% in newly diagnosed Major Depressive Disorder patients and after three months of antidepressive medication. Methods: This prospective study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU) from January to December, 2014 to assess the lung function status in MDD patients. For this, 30 newly diagnosed MDD patients (Group B1), age 20 to 50 years were enrolled from the Department of Psychiatry of BSMMU. FEF25%-75% of all subjects were assessed by a portable digital spirometer (PONY FX, Cosmed, Italy) before and after (Group B2) three months of giving antidepressive medication. For statistical analysis, paired sample't' test was done and p value 0.05 is considered as level of significance. Results: There was no significant change found in patients taking antidepressive medication when compared between before and after three months of medication. Conclusion: From this study it may be concluded that there is no role in antidepressive medication in improvement of depressed lung function in major depressive disorder KYAMC Journal Vol. 8, No.-1, Jul 2017, Page 53-55